Behavioral profiling of SLC38A10 knockout mice using the multivariate concentric square fieldTM test - Lindberg, Frida A.; Roman, Erika; Fredriksson, Robert (Frontiers in Behavioral Neuroscience, 2022)
SLC38A10 is a gene that encodes the SLC38A10 protein, also known as SNAT10. The SLC38 family is evolutionary old, and SLC38A10 is one of the oldest members within the family. It is ubiquitously expressed, and its substrates are glutamine, glutamate, alanine, aspartate, and serine. However, little is known abouts its biological importance. In the current study, a SLC38A10 knockout mouse was run in the multivariate concentric square field™ (MCSF) test. The MCSF test gives the mouse a choice of areas to explore; sheltered areas, elevated and illuminated areas or open spaces, and a behavioral profile is obtained. There was not a pronounced difference in the behavioral profile in SLC38A10 knockout mice compared to their WT controls, although subtle alterations in zones associated with exploratory behavior and risk assessment in female and male knockout mice, respectively, could be observed.